PERAN KHUSUS VERBA “MENARIK” DALAM BAHASA BALI KAJIAN METABAHASA SEMANTIK ALAMI (Widyadari : Jurnal Pendidikan, 2021)
Verb ‘To pull’is one of Balinese language kinds in this research. Verb ‘To pull’ within in Balinese language (VMBB) is verb withsome lexicon having distinctive meaning elements. VMBB is a unique verb. Verb is often to found in daily lifes. However, it needs to be understood to avoid the misunderstanding in using the lexicon. The researcher was found the use of different lexicon but in the same field meaning, they are: ngedeng, maid, matek, ngered, medeng, ngabud, ngembot, ngembat, ngangget and ngaud. Lexicons have different aimsbased on its function. Based on the semantic roles was found verb ‘To pull’ within in Balinese language (VMBB) especially in specific role. The specific role was categorized by actor and undergoer. Actor was called as agent because of influence, control, and manage the events of ‘To pull’. But, undergoer have specific roles as patient because of receiving the action by agent and changing physical by the affect of action direclty.